Pemodelan Kinerja Simpang Sebidang Bersinyal Menggunakan Perangkat Lunak Vissim - Sarwanta Sarwanta; Hamdani Abdulgani (Jurnal Rekayasa Infrastruktur, 2023)
A signalized level intersection is the meeting point for vehicles heading towards the intersection and vehicles leaving the intersection. The problem at road intersections is the potential for queues and delays because vehicles will reduce their speed when passing through the intersection. Traffic control at signalized intersections is by using signals or traffic lights with the aim of minimizing queues and delays. As time goes by, there is an increase in traffic volume, this will result in a decrease in intersection performance, so an evaluation of intersection performance needs to be carried out. The aim of this research is to evaluate the performance of one of the signalized intersections in the city of Balikpapan, namely Simpang Lab Coal/BDS, in existing conditions and in the next 5 years. Evaluation of the performance of this intersection uses the guidelines of the Indonesian Road Capacity Manual (MKJI 1997) and modeling using Vissim software. The results of the performance evaluation based on MKJI 1997 in existing conditions showed that the intersection capacity was 4854.6 pcu/hour. The degree of saturation was obtained at 1.003, the intersection delay was 49.7 pcu/sec, the average queue length was 36.80 m. The results of modeling using Vissim software, in existing conditions, the average queue length is 60 meters. the average delay at the intersection is 17 pcu/sec and the intersection performance is at level of service C. At the intersection conditions in the next 5 years, the queue length is obtained at 144 meters, the largest